Death & Texas: Dark is the Night - Book 2 - Johnstone, William W.; Johnstone, J. A. (New York, NY : Pinnacle Books, Kensington Publishing Corp., 2019)
"There are a million ways to die in the great state of Texas. And on the lawless streets of New Hope, the odds are even worse. Once the home of Comanche, the region has been up for grabs since the settlers drove off the natives. Now its a magnet for settlers looking for cheap land, merchants looking to exploit its resources--and outlaws looking for a place to hide in between robbing and killing. With shootouts and showdowns being a nightly occurrence, its one of the deadliest places on earth. And the governor aint happy about it. He wants to clean up the town. He wants to wipe away the scum. And he knows just the man to do it.... Enter Cullen McCabe. A small- town sheriff turned special agent, McCabe doesnt care what he has to do--or who he has to kill--to rid this hellhole of every rustler, robber, and ruthless cuss in sight. Especially the notorious Viper Gang...." -- Back cover.
Keywords: Outlaws -- Fiction; Corruption -- Fiction; Texas -- Fiction; Western fiction